Gambar Allah Menurut Kejadian 1: Sebuah Penolakan terhadap Alienasi Subjek dan Domestikasi Gambar Allah - Tony Wiyaret Fangidae (STFT Jakarta, Indonesia, 2020)
A constructive understanding of the image of God is influenced by two important events that is experienced by the Israelites: colonization in Egypt and alienation in Babylon. These two influences are problematic when we absolve them to read the story of human creation in Genesis 1. This article attempts to overcome the problem through a post-exilic perspective on the image of God in Genesis 1. This article concludes that the implication of the image of God rejects the alienation and domestication of God’s image.